The birth satisfaction scale: Turkish adaptation, validation and reliability study - (:unkn) unknown (KARE PUBL, 2015)
OBJECTIVE: The objective of this study is to investigate the validity and the reliability of Birth Satisfaction Scale (BSS) and to adapt it into the Turkish language. This scale is used for measuring maternal satisfaction with birth in order to evaluate women's birth perceptions. METHODS: In this study there were 150 women who attended to inpatient postpartum clinic. The participants filled in an information form and the BSS questionnaire forms. The properties of the scale were tested by conducting reliability and validation analyses. RESULTS: BSS entails 30 Likert-type questions. It was developed by Hollins Martin and Fleming. Total scale scores ranged between 30-150 points. Higher scores from the scale mean increases in birth satisfaction. Three overarching themes were identified in Scale: service provision (home assessment, birth environment, support, relationships with health care professionals); personal attributes (ability to cope during labour, feeling in control, childbirth preparation, relationship with baby); and stress experienced during labour (distress, obstetric injuries, receiving sufficient medical care, obstetric intervention, pain, prolonged labour and baby's health). Cronbach's alfa coefficient was 0.62. CONCLUSION: According to the present study, BSS entails 30 Likert-type questions and evaluates women's birth perceptions. The Turkish version of BSS has been proven to be a valid and a reliable scale.
Keywords: Birth; reliability; satisfaction; validity